CRISPR-Cas9-Based Discovery of the Verrucosidin Biosynthesis Gene Cluster in Penicillium polonicum - Valente, Silvia; Piombo, Edoardo; Schroeckh, Volker; Meloni, Giovanna Roberta; Heinekamp, Thorsten; Brakhage, Axel A.; Spadaro, Davide (Frontiers in Microbiology, 2021)
Penicillium polonicum, commonly found on food matrices, is a mycotoxigenic species able to produce a neurotoxin called verrucosidin. This methylated α-pyrone polyketide inhibits oxidative phosphorylation in mitochondria and thereby causes neurological diseases. Despite the importance of verrucosidin as a toxin, its biosynthetic genes have not been characterized yet. By similarity analysis with the polyketide synthase (PKS) genes for the α-pyrones aurovertin (AurA) and citreoviridin (CtvA) 16 PKS genes for putative α-pyrones were identified in the P. polonicum genome. A single PKS gene, verA, was found to be transcribed under verrucosidin-producing growth conditions. The annotated functions of the genes neighbouring verA correspond to those required for verrucosidin biosynthesis. To prove the involvement of verA in verrucosidin biosynthesis, the clustered regularly interspaced short palindrome repeats (CRISPR) technology was applied to P. polonicum. In vitro reconstituted CRISPR-Cas9 was used to induce targeted gene deletions in P. polonicum. This approach allowed identifying and characterizing the verrucosidin biosynthetic gene cluster. VerA deletion mutants were no longer able to produce verrucosidin, whereas they were displaying morphological characteristics comparable with the wild-type strain. The available CRISPR/Cas9 technology allows characterising the biosynthetic potential of P. polonicum as valuable source of novel compounds.